Optimalisasi Penggunaan Metode Fundraising dalam Memperoleh Dana Zakat, Infaq dan Shodaqah - Abdul Manaf; Risti Lia Sari; Maskudi Maskudi (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2021)
Nahlatul Ulama is an Islamic community organization that not only spreads Islamic teanchings, but also acts as a community facilitator in the religious, social, economic and educational fields. In an effort to become a community facilitator in the social sector, NU established the amil zakat infaq and shodaqah Nahdlatul Ulama (LAZISNU) Institude which is tasked with collecting, managing and distributing social services to people in need. The research focuses on how the fundraising method is used in raising funds. The formulation of the problem is (1) how is the LAZISNU-CARE fundraising method in Semarang city in obtaining zakat, infaq and shodaqah fund? (2) what are the supporting and inhibiting factors of LAZISNU in Semarang city in obtaining zakat, infaq and shodaqah fund? To answer this question, the type of research used in this research is qualitative. The sources of research data used are primary data sources and secondary data. Data collections tecniquies used include observation, interviews and documentation, technical data analysis using data reduction, data presentation, data verification, drawing conclusions. The results of this study indicate that (1) in conducting fundraising LAZISNU-CARE Semarang City uses two methods, namely the direct fundraising method and the indirect fundraising method. (2) the supporting factors are the factors of coomperation with branch leaders in the city of semarang, the existence of a transparent reporting system, the existence of payments through accounts, the awareness of muzakki to tithe. While the inhibiting factors are the lack of public knowledge about the obligation to pay zakat other than zakat fitrah, as well as the abundance of direct distribution by muzakki.